IMPLEMENTASI APLIKASI PENGENALAN SOP PENGOLAHAN LIMBAH INDUSTRI PT X BERBASIS ANDROID - DEROSARI, ROSALINDA MENTIGASA DEROSARI; Handoko, Koko (Computer Science and Industrial Engineering, 2024)
B3 medical waste management raises specific considerations and can provide a major problem if not handled effectively. As a result, PT. Desa Air Cargo Batam is on hand to undertake the processing, and the company already holds a B3 industrial waste processing authorization. To meet the company's vision and objective, the correct Standard Operating Procedure (SOP) must be used to reduce negative affects on the environment and society. However, in these companies, awareness and comprehension of the Standard Operating Procedure (SOP) for the handling of B3 medical waste remains a concern that must be addressed. The Software Development Life Cycle (SDLC) research technique was utilized for software development, and application development in this study was done with Adobe Illustrator, Visual Studio Code, and Flutter. The resulting application is compatible with Android smartphones running at least version 8.0 (Oreo). The waterfall method is applied in this scenario. The findings of black-box testing and functional testing reveal that the application performed as predicted, and the results of this application questionnaire are in the very good category, with no problems when operating